2021
DOI: 10.1159/000514662
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Outcomes after Phacoemulsification in Eyes with Good Visual Acuity before Cataract Surgery

Abstract: Objective: To analyze cataract surgery outcomes and related factors in eyes presenting with good visual acuity. Subject and Methods: Retrospective longitudinal of patients undergoing phacoemulsification between the years 2014-2018 in Moorfields Eye Hospital and satellite units. Pre- and postoperative visual acuity (unaided, with glasses, with pinhole) were analyzed. Inclusion criteria were age≥40 years and pinhole visual acuity ≥6/9 preoperatively. Exclusion criteria were no postoperative visual acuity data. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Consistent with several published studies [14,[30][31][32] our study showed a signi cant association between postoperative surgical complications and poor visual outcomes. More precisely, persons with complications after surgery were four times more likely to experience low visual outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with several published studies [14,[30][31][32] our study showed a signi cant association between postoperative surgical complications and poor visual outcomes. More precisely, persons with complications after surgery were four times more likely to experience low visual outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…A multiple regression analysis by Khanna et al revealed that patients with postoperative complications (POC) were two times more likely to experience worsen visual outcome [14]. Similarly, Dervenis and coworkers observed that persons that suffered postsurgical complications such as vitreous loss had a signi cantly compromised postoperative visual acuity with reduced outcomes [30]. Likewise, Mimouni et al, demonstrated an independent association between preexisting postoperative complications and poor vision outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, mean visual acuity improved from 20/80 preoperatively to 20/60 on postoperative Day 1 and to 20/40 thereafter. A study conducted at Moorfield Eye Hospital reported that visual acuity improved from 0.5 (20/60) to 0.2 (20/30), similar to our findings [ 18 ]. Another cross-sectional study assessed the difference in visual acuity between patients with and without diabetes, reporting that 87% of those with diabetes achieved normal vision (20/20 to 20/60) on postoperative Day 1, in contrast to 92% of those without diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…However, an increasing age is associated with worse VA outcomes following cataract surgery. With each additional year of age, the patients had a 0.96-fold lower likelihood of attaining a VA of ≥6/9 on the Snellen chart [21]. Although our study did not compare the VA before and after surgery, our study suggests that cataract surgery should be recommended at a proper time.…”
Section: Discussionmentioning
confidence: 69%